2021
DOI: 10.1039/d1cc04417f
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of liquid structure and controlling molecular diffusion using supramolecular constructs

Abstract: The non-equilibrium liquid structure was achieved by interfacial jamming of pillar[5]arene carboxylic acid (P[5]AA) mediated by hydrogen bonding interactions. The assembly was reversibly modulated via jamming to unjamming transition thus...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…A series of aromatic aldehydes with a varying number of aldehyde groups were synthesized, namely, 4,4′,4″-((1,3,5-triazine-2,4,6-triyl)tris(oxy))tribenzaldehyde, 4,4′-((6-methoxy-1,3,5-triazine-2,4diyl)bis(oxy))dibenzaldehyde, and 4-((4,6-dimethoxy-1,3,5triazin-2-yl)oxy)benzaldehyde, following the procedure reported in the literature (see the Supporting Information, Schemes S1−S3), and were termed as TBZ, DBZ, and SBZ, respectively, as shown in Scheme 1. The characterization of these compounds, such as 1 H, 13 C NMR, and IR, is provided in the Supporting Information Figures S1−S9. To assess the interfacial activity of the aldehydes and PEI, a stock solution of 1.0 mg/mL aldehydes in 1,2-dichlorobenzene (DCB) and 1% w/w aqueous solution of PEI were prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of aromatic aldehydes with a varying number of aldehyde groups were synthesized, namely, 4,4′,4″-((1,3,5-triazine-2,4,6-triyl)tris(oxy))tribenzaldehyde, 4,4′-((6-methoxy-1,3,5-triazine-2,4diyl)bis(oxy))dibenzaldehyde, and 4-((4,6-dimethoxy-1,3,5triazin-2-yl)oxy)benzaldehyde, following the procedure reported in the literature (see the Supporting Information, Schemes S1−S3), and were termed as TBZ, DBZ, and SBZ, respectively, as shown in Scheme 1. The characterization of these compounds, such as 1 H, 13 C NMR, and IR, is provided in the Supporting Information Figures S1−S9. To assess the interfacial activity of the aldehydes and PEI, a stock solution of 1.0 mg/mL aldehydes in 1,2-dichlorobenzene (DCB) and 1% w/w aqueous solution of PEI were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Once the assemblies are formed, the interface can be transformed into various nonequilibrium structures. , These structured liquids can hold their nonequilibrium shape indefinitely when the interface is compressed . In recent years, noncovalent supramolecular interactions such as hydrogen bonding, electrostatic, , charge transfer, and host–guest interactions have been utilized to structure the liquid–liquid interface. The inherent dynamic and reversible nature of supramolecular interactions allowed the integration of stimuli-responsive behaviors into the interfacial assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [27] phase, even up to 1000 mM NaCl (Figure 5b), as well as acidic (Figure 5c) or alkaline (Figure 5d) conditions with pH values ranging from 1.0 to 12.5. This work is the first attempt to construct nonionic surfactants for the structuring liquids, providing a novel template and design strategy for supramolecular-based surfactants.…”
Section: Hydrogen Bonding Interaction and Van Der Waals Forcementioning
confidence: 99%
“…[25] Recently, Varshney et al reported the fabrication of a supramolecular material through another type of hydrogen bonding (À OÀ H•••OÀ ), that could be used to structure liquids. [27] P [5]AA, an acid derivative of pillar [5]arene, having ten carboxylic acid groups, can form stable NPSs by intermolecular hydrogen bonding under acidic conditions with pH values ranging from 2 to 4 (Figure 4a/4b). Under alkaline conditions, the P [5]AA behaves like a macrocyclic anion and electrostatic repulsions lead to a disruption of hydrogen bonding interactions.…”
Section: Multiple Hydrogen Bonding Interactionsmentioning
confidence: 99%
“…While the studies of Hou et al and Varshney et al showed it is possible to structure liquids without ligands, [25,27] using simple molecular surfactants to structure liquids remains a challenge. Hata et al demonstrated that liquids can be structured by using a nonionic crystalline surfactant n-octyl cello-oligosaccharide (Cell-C8) that can form a crystalline monolayer at the water-organic solvent interface by intermolecular hydrogen bonding and van der Waals forces (Figure 5).…”
Section: Hydrogen Bonding Interaction and Van Der Waals Forcementioning
confidence: 99%